Formulasi Sediaan Sheet Mask Ekstrak Daun Murbei (Morus alba L.) sebagai Anti Acne Terhadap Bakteri Propionibacterium acnes - Nurul Aina Harahap; Ulfayani Mayasari; Rizki Amelia Nasution (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2024)
This study aimed to determine the antibacterial activity of mulberry leaf extract and formulate Sheet Masks containing the extract at different concentrations of 4%, 6%, 8%, and 10%. The method involved antibacterial activity testing using the disk diffusion method with positive control (clindamycin and Wardah Sheet Mask), negative control (DMSO), and three replications. Organoleptic and physical evaluations of the Sheet Mask formulation were also conducted. The results showed that mulberry leaf extract inhibited the growth of Propionibacterium acnes, with inhibition zones of 6.0 mm at 4%, 9.45 mm at 6%, 12.57 mm at 8%, and 13.95 mm at 10%. For the Sheet Mask formulations, the inhibition zones were 10.69 mm for the positive control (clindamycin), 0.1 mm for F0, 9.78 mm for F1 (8%), and 10.29 mm for F2 (10%). Organoleptic evaluation revealed that the most preferred formulations in terms of color, aroma, and texture were F0, F2, and F1, respectively. Physical evaluation confirmed that the Sheet Mask formulations met quality standards. In conclusion, mulberry leaf extract demonstrated antibacterial activity against Propionibacterium acnes, with the most effective concentrations being 8% and 10%. Keywords: antibacterial, acne, Sheet Mask, mulberry, Propionibacterium acnes